Did plate tectonic changes lead to the emergence of hominid bipedalism? - Ben-Avraham, Zvi; Rak, Joel; Schubert, Gerald; Lodolo, Emanuele; Schattner, Uri (Frontiers in Environmental Archaeology, 2024)
When early hominids began walking upright around 6 Ma, their evolutionary course took a sharp turn. The new posture enabled physical and mental developments that had not been possible before. The factors driving the transition from quadrupedalism to bipedalism remain open. Most studies have linked this fundamental transition to environmental, topographical, geomorphological, and climatic changes that progressively transformed jungle- and forest-dominated areas of southern and eastern Africa into vast savannas, thus partitioning ecological niches. During the same timeframe, major tectonic events occurred worldwide within a relatively short geological period, due to a significant and sudden shift in the motion of the Pacific plate. In our previous work, we coined the term ripple tectonics to link a major tectonic impact to the short-term local events it caused worldwide. In this work, we link the tectonic trigger that initiated the ripple tectonic cascade in the Pacific with the radical environmental changes that could have driven hominids to develop a bipedal posture.